COVID-19, jobs and the future of work in the LDCs: A (disheartening) preliminary account - Aurelio Parisotto; Adam Elsheikhi (International Labour Organization (ILO), 2020)
This paper provides an overview of the evolution of the COVID-19-induced health and labour market crises in the Least Developed Countries (LDCs), drawing on a large set of available data and sources. It highlights how the outbreak is affecting jobs and incomes via multiple channels of transmission. It looks at policy responses so far and provides some suggestions for national employment and economic policies, as well as international support to help LDCs on their path to a job-rich recovery and future resilience @While the effects of the outbreak of the COVID-19 pandemic in the most advanced nations are receiving much attention, the Least Developed Countries (LDCs) are at risk of suffering the most severe economic and social damages. Plummeting exports and drops in tourism and remittances, coupled with even a few weeks of lockdown, are profoundly affecting labour markets in LDCs, not least because most people work informally, have little cash reserves, no paid sick leave, no access to teleworking and nothing to fall back on. At the same time, governments have limited fiscal space available to provide relief to individuals and enterprises. This paper provides an overview of the evolution of the health and labour market crises in the LDCs, drawing on a large set of available data and sources. It highlights how the outbreak is affecting jobs and incomes via multiple channels of transmission. It looks at policy responses so far and provides some suggestions for national employment and economic policies, as well as international support to help LDCs on their path to a job-rich recovery and future resilience
Keywords: 330; labour economics; employment policy; migrant workers; unskilled workers; working conditions; hours of work; social justice; vulnerable groups; COVID-19; safety management